Do there exist definitive philosophical arguments? (Diametros, 2004)
The article considers the problem of the existence and the nature of definitive methods for justifying philosophical claims, for during the last thousand years philosophy seems to have revolved around the same problems and none of them has been definitively solved. The author analyzes various methods for justifying philosophical claims, the nature of philosophy in the light of the distinctions between analytic vs. synthetic and a priori vs. a posteriori knowledge, and proposes an interpretation of the concept of "intuition" as a solution of the problem formulated in the title.